Warning Method of Coal Bursting Failure Danger by Electromagnetic Radiation - Guang-Jian Liu; Cai-Ping Lu; Hong-Yu Wang; Peng-Fei Liu; Yang Liu (Shock and Vibration)
Electromagnetic radiation (EMR) can reflect the stress state and deformation level of coal, yet its warning indexes correlated with coal properties and roof caving is poorly understood. The laboratory observations of EMR effects of coal samples bursting failure and in situ investigations in the process of roof caving are presented in this paper. EMR peak with increasing stress is discussed when the failure of coal samples happens, which provides an explanation to EMR signals positively correlated well with the stress loaded. The linearly increasing relation is also found between EMR intensity and the uniaxial compressive strength, and EMR maximum amplitudes and pulses behave a logarithmic accretion tendency with bursting energy indexes of coal. By in situ investigations, it is well found that EMR amplitude can effectively warn coal deformation and failure based on the critical value 120 mV proposed from experiments.